NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Muhammad Haris; Oskar Hutagaluh; Elsa Mulya Karlina (CV. ADIBA ASIHA AMIRA, 2024)
This research aims to describe the values of moral education towards Allah SWT in the novel About You by Tere Liye, the values of moral education towards fellow humans in the novel About You by Tere Liye, the values of moral education towards yourself in the novel About You Tere Liye's work. This research uses a qualitative approach with a library research type of research, data collection techniques using document analysis. The data analysis technique used is content analysis. The results of the research show that: 1) The values of moral education towards Allah SWT in the novel About You by Tere Liye are as follows: Faith, piety, sincerity, and gratitude. 2) The values of moral education towards fellow humans in the novel About You by Tere Liye are as follows: Friendship, Fairness, Kindness, Please Help, and Birrul Walidain. 3) The values of moral education towards oneself in the novel About You by Tere Liye are as follows: Shiddiq, Trustworthiness, Patience, Independence, and Hard Work.